2022
DOI: 10.1007/s11033-022-07183-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of sodium glucose co-transporter -2 inhibitors from a renin–angiotensin–aldosterone system perspective in patients infected with COVID-19: contextualizing findings from the dapagliflozin in respiratory failure in patients with COVID-19 study

Abstract: Numerous studies demonstrate parallels between CVD, type 2 diabetes mellitus (T2DM) and COVID-19 pathology, which accentuate pre-existing complications in patients infected with COVID-19 and potentially exacerbate the infection course. Antidiabetic drugs such as sodium-glucose transporter-2 (SGLT-2) inhibitors have garnered substantial attention recently due to their efficacy in reducing the severity of cardiorenal disease. The effect of SGLT-2 inhibitors in patients with COVID-19 remains unclear particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…50 Recent studies suggest possible beneficial effects of noninsulin antihyperglycemic agents against SARS-CoV-2 infection, such as dipeptidyl peptidase-4 inhibitors (DPP4i), sodium-glucose cotransporter-2 inhibitors (SGLT2i), and glucagon-like peptide-1 (GLP-1) receptor agonists. [51][52][53][54][55] The current study has several limitations: (i) more examinations with human ACE2-transgenic mice might be considered to confirm the conclusion of this study. (ii) This experimental model is limited with respect to pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Recent studies suggest possible beneficial effects of noninsulin antihyperglycemic agents against SARS-CoV-2 infection, such as dipeptidyl peptidase-4 inhibitors (DPP4i), sodium-glucose cotransporter-2 inhibitors (SGLT2i), and glucagon-like peptide-1 (GLP-1) receptor agonists. [51][52][53][54][55] The current study has several limitations: (i) more examinations with human ACE2-transgenic mice might be considered to confirm the conclusion of this study. (ii) This experimental model is limited with respect to pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has shown that there is no association between mineralocorticoid receptor antagonist usage and mortality in COVID‐19 50 . Recent studies suggest possible beneficial effects of noninsulin antihyperglycemic agents against SARS‐CoV‐2 infection, such as dipeptidyl peptidase‐4 inhibitors (DPP4i), sodium‐glucose cotransporter‐2 inhibitors (SGLT2i), and glucagon‐like peptide‐1 (GLP‐1) receptor agonists 51–55 …”
Section: Discussionmentioning
confidence: 99%
“…The increasing prevalence of e-cigarette use among adolescents, particularly teenagers, is emerging as a significant public health concern [37,38]. In 2014, the use of e-cigarettes among young adults (18-24 years old) surpassed that among adults aged 25 years and older.…”
Section: Increasing Prevalence Of E-cigarette Use Among Adolescentsmentioning
confidence: 99%
“…Metformin and DPP-4 inhibitors have been shown to have beneficial effects in the COVID-19 treatment [ 26 28 ]. Although the use of SGLT2 inhibitors in COVID-19 is still controversial, there is no clear evidence that they increase mortality and progression in COVID-19 [ 29 ]. However, there is also no evidence proving that SGLT2 inhibitors have a beneficial effect on COVID-19 [ 2 ].…”
mentioning
confidence: 99%